[Rezension von: Anne Dunlop (Ed.), Antipodean Early Modern] - Legaré, Anne-Marie 1950- (2019)
Rezension zu: Anne Dunlop (Ed.); Antipodean Early Modern. European Art in Australian Collections, c. 1200-1600; Amsterdam: Amsterdam University Press 2018; 296 p.; ISBN 978-9462985209